[Icelandic Airlines Airplane at Keflavik] - Streng, Evelyn Fiedler (1977)
Photograph of an airplane of an Icelandic Airline at Keflavik. The white, brown, and yellow striped plane sits stationary on wet asphalt with a white staircase full of people exiting the airplane at its front door. The Icelandic text reading "Loftleidir Icelandic" is written across the plane's side. A white building with several colorful vehicles are visible in the background from under the plane.